Moderate Student Construction: A Study on Moderate Islamic Views and Practices Among Intellectuals in Islamic Higher Education in West Papua - Yudiawan, Agus; Rasyid, Muhammad Rusdi; Arifin, Miftah; Ahmadi; Syahrul (JURNAL PENELITIAN, 2024)
Various efforts have been made by the leadership of Islamic Higher Education institutions to prevent the infiltration of radical ideologies on their campuses. These efforts range from internalizing religious moderation to monitoring deviant student organizations, both of which have been intensively pursued by institutional leaders. However, since the declaration of these initiatives, there has been no empirical evaluation to assess whether students in Islamic Higher Education, particularly in Papua and West Papua, have a proper understanding of the concept of moderate Islam. This gap could hinder policymakers' ability to effectively combat the spread of radical ideas. This study employs a mixed-method approach, surveying 1,309 students from three Islamic Higher Education institutions in West Papua: IAIN Sorong, STIT Yapis Manokwari, and STAI Al Mahdi Fakfak. The quantitative component consists of surveys designed to evaluate key indicators of religious moderation, including tolerance, anti-violence attitudes, and national commitment—critical factors that influence pro-violent extremism views in Islamic Higher Education. Additionally, qualitative studies were conducted through focus group discussions with selected key informants to gain deeper insight into the students' understanding, actions, and efforts to build moderation capacity. The study’s findings revealed that, although students' knowledge of religious moderation is relatively high, the factors of tolerance and anti-violence attitudes are strong predictors of pro-violent extremism. Therefore, it is essential to strengthen the role of "moderation houses" from an institutional perspective, and integrated programs must serve as the foundation for building religious moderation capacity, particularly for students in Islamic Higher Education.